Model of lie cues detection in cross-cultural communication: insights from linguistic and cultural intersections - Arung, Fernandes; Boeriswati, Endry; Eriyani, Reni Nur; Murtadho, Fathiaty (UNIB Press, 2025)
This study explores lie detection within cross-cultural communication by examining linguistic and cultural cues that indicate deception. Employing a qualitative approach with an explanatory comparative method, the research involved six participants from diverse ethnic backgrounds in Southeast Sulawesi, Indonesia. Data were collected through observation and interviews using audio-visual scenarios designed to elicit both honest and deceptive responses. The findings reveal that linguistic cues to deception include uncertainty in speech, changes in intonation, unsynchronized eye contact and body language, and the use of ambiguous or vague expressions. Cultural cues also play a critical role, with norms, values, and traditions shaping how individuals express and interpret lying behaviors. For example, avoiding eye contact may signal dishonesty in one culture but signify respect in another. The research highlights that lie detection strategies grounded in single-cultural paradigms are insufficient for multicultural contexts. As a solution, the study proposes a new model that integrates linguistic and cultural parameters, offering a holistic framework for more accurate lie detection in intercultural settings. This integrated model contributes to both theoretical and practical domains, including law enforcement, diplomacy, and international business, where cultural sensitivity is essential. By advancing understanding of how language and culture interact in deceptive communication, the study addresses a critical gap in the literature and promotes more equitable and effective approaches to detecting deception in global interactions.